The multiplicity of physicians' professional linkages in the Brazilian health system: A social network analysis perspective - de Oliveira Gobbo, Simone Cristina [UNESP]; Junior, José Alcides Gobbo [UNESP]; Musetti, Marcel Andreotti (My University, 2018)
In health literature, there is a paucity of studies that examine physicians' network of professional linkages in the public and private health sector. Therefore, there is a need to further investigate how the multiplicity of physicians' professional linkages shapes health network structures. The use of Social Network Analysis (SNA) tools in this context promises to be a fruitful line of inquiry with clear theoretical and practical implications. The study in a Brazil's public health care system is a unique context, because the lack of equipment, scarcity of resources for educational training and restrictive occupational licensing regulations causes the multiplicity of physicians' professional linkages. The results of this study presents some interesting conclusions in regard to the physician's professional linkages and their results in the physician's network structure. The overall size of the network structure is large, consisting of 789 actors. These results suggest that physicians with more professional linkages probably declare more different professional occupations. In regard to network centralisation and degree centrality, the results indicate that connections in this network are relatively centralized in one or more physicians, however the overall density is low, indicating that connections are somewhat redundant. Establishing policies, such as determination of limits to the number of professional linkages per physician and limits to weekly workload in the public health care system would lead to improve the efficiency of the overall network. © 2018 Nova Science Publishers, Inc.
Keywords: Brazilian health system and physicians' professional linkages; Social network analysis